USP14 inhibition by degrasyn induces YAP1 degradation and suppresses the progression of radioresistant esophageal cancer - Fang Yuan; Juan Xu; Lingmei Xuan; Chan Deng; Wei Wang; Rong Yang (Neoplasia: An International Journal for Oncology Research, 2025)
Background: Radiotherapy is a major modality for esophageal cancer (ESCA) treatment, yet radioresistance severely hampers its therapeutic efficacy. Ubiquitin-specific peptidase 14 (USP14) is a novel deubiquitinase and can mediate cancer cells’ response to irradiation, although the underlying mechanism remains unclear, including in ESCA. Methods: To evaluate the expression of USP14 in ESCA tissues or cells, we used RNA-Seq, immunoblotting, co-immunoprecipitation (Co-IP), ubiquitination, quantitative real-time polymerase chain reaction (qRT-PCR), and immunofluorescence assays in this investigation. Additionally, we used CCK8, cloning, and migration tests to examine the proliferation and migration of ESCA cells. We also used transplantation tumor mouse model to investigate the course of the cancer cell growth. Finally, we looked into the biological processes linked to USP14 using gene set enrichment analysis (GSEA), which was later verified. Results: We observed a significant upregulation of USP14 in human ESCA tissues and cell lines, especially in those with radioresistance. Moreover, USP14 knockdown significantly restrained the proliferation and inhibited the radiation tolerance of ESCC cells. Here, we identified a potential inhibitor of USP14, Degrasyn (DGS), and investigated its regulatory effects on ESCA radioresistance and progression. We found that DGS had marked antiproliferative effects in radiosensitive ESCA cell lines. Notably, a low dose of DGS significantly enhanced the sensitivity of radioresistant ESCA cells to irradiation, as shown by the significantly reduced cell proliferation, migration, and invasion. Furthermore, the combination of DGS and X-ray irradiation strongly induced DNA damage in radioresistant ESCA cell lines by increasing the phosphorylation levels of H2AX (γ-H2AX) and checkpoint kinase 1/ataxia-telangiectasia-mutated-and-Rad3-related kinase (CHK1/ATR) signaling. Animal experiments confirmed the effective role of the DGS and X-ray combined treatment in reducing tumor growth and irradiation tolerance of ESCA in vivo with undetectable toxicity. Importantly, the promotive and malignant biological behaviors of ESCA cells suppressed by the DGS/X-ray combination treatment were almost eliminated by USP14 overexpression, along with the abolished DNA damage process. Mechanistically, we found that USP14 could interact with Yes-associated protein 1 (YAP1) and induce its deubiquitination in radioresistant ESCA cells. Interestingly, we discovered that DGS/X-ray co-therapy significantly reduced the stability of YAP1 and induced its ubiquitination in radioresistant ESCA cells. More importantly, the proliferation, epithelial-mesenchymal tansition (EMT) process, and DNA damage regulated by DGS/X-ray and USP14 knockdown were significantly eliminated when YAP1 was overexpressed in radioresistant ESCA cells. Conclusions: These data revealed the potential role of DGS/X-ray co-therapy in controlling ESCA resistance to radiotherapy by inhibiting the USP14/YAP1 axis, providing a candidate strategy for ESCA treatment.